(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The effectiveness of using apneic high-flow oxygenation above the glottis combined with intermittent endotracheal intubation in anesthesia management for laryngeal and tracheal Papilloma surgery. Subjects and methods: Prospective, cross-sectional, non-controlled clinical intervention study. Study on 86 patients undergoing general anesthesia for laryngeal and/or tracheal Papilloma surgery over an 8 months period. Using high-flow oxygen alternately with endotracheal intubation to ventilate patients. Recorded parameters: changes in SpO2, EtCO2, vital signs, surgery time, apnea time, possible complications. Results: Mean surgery time was 62.93 ± 11.29 minutes, mean apnea time was 17.05 ± 7.42 minutes. During intervention phases, SpO2 was > 97% overall, higher than preoperative numbers with statistical significance, p < 0,001. End of the apnea period, mean EtCO2 value was 54.74 ± 7.56 mmHg, higher than normal but still significantly lower than the patient’s initial value. Hemodynamic stability, no significant complications. Conclusion: The patients’ airway was completely controlled, favorable for surgery. Sufficient oxygen was provided during surgical anesthesia, no significant complications.